2009
DOI: 10.1002/app.31031
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the structure of a porous polymer by coupling supercritical CO2 and single screw extrusion process

Abstract: A study on the extrusion of Eudragit E100 was carried out using supercritical carbon dioxide (scCO 2 ) as plasticizer and foaming agent. ScCO 2 modifies the rheological properties of the material in the barrel of the extruder and acts as a blowing agent during the relaxation when flowing through the die. For experiments, a singlescrew extruder was modified to be able to inject scCO 2 within the extruded material. The aim is to determine a correlation between operating conditions and foam structure. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…Finally, each of the polymers investigated exhibited increased dissolution rates when processed with CO 2 injection due to the increased porosity and foaming effect of the expanding gas upon exiting the extruder die. Other investigators have found that the pore size is a function of the processing temperature and CO 2 concentration (89).…”
Section: Temporary Plasticizers and Supercritical Technologymentioning
confidence: 95%
“…Finally, each of the polymers investigated exhibited increased dissolution rates when processed with CO 2 injection due to the increased porosity and foaming effect of the expanding gas upon exiting the extruder die. Other investigators have found that the pore size is a function of the processing temperature and CO 2 concentration (89).…”
Section: Temporary Plasticizers and Supercritical Technologymentioning
confidence: 95%
“…[9,10] The single-screw extruder has a 30-mm screw diameter and a length to diameter (L/D) ratio of 35 (Rheoscam, SCAMEX, Crosne, France). A large L/D ratio generally allows increasing not only the capacity of mixing and melting but also energy consumption.…”
Section: Methodsmentioning
confidence: 99%
“…[8] Lately, Nikitine et al studied the correlation between operating conditions and foam structures of Eudragit E100. [9] This work was also completed by the study of the influence of scCO 2 on the polymer flow of Eudragit E100 in the extruder. [10][11][12] Lipid soluble chemicals, such as carvedilol (CAR), are almost insoluble in water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a new sc CO 2 assisted extrusion process, microcellular foams of a biocompatible amorphous polymer were elaborated [8]. However, understanding and improving such a process requires the knowledge of physical properties, like the solubility of CO 2 into the polymer, the diffusion coefficient and the viscosity of the mixture.…”
Section: Introductionmentioning
confidence: 99%